MORAL FORMATION BASED ON HABITUATION AND EXAMPLE (Case Study in MAN 2 Kuningan Ciawigebang Kuningan West Jawa) - Siti Nurjanah (International Conference on Economic Business and Social Science, 2023)
The purpose of this study was to determine the moral formation of learners based on habituation and exemplary, and to determine the success of the formation of habitual morals and exemplary in MAN 2 Kuningan, West Java. The author uses a qualitative method with a phenomenological approach, so in collecting data, the author uses observation techniques, in-depth interviews, documentation and using the data technique child can data model Miles and Huberman. Habit based and exemplary moral formation in MAN 2 Kuningan West Java was carried out with various activities, namely: Habit of dhuhur prayer in congregation, habituation of Infaq every Friday morning, habituation of Asr prayer in congregation, habituation of tadarus al-Qur'an, habituation of tahfizd together every Monday the flag ceremony is over, habituation of yasinan and khitobah (lectures) every Friday morning, habituation in dress. The exemplary moral-based formation is carried out with various activities, namely: discipline, honesty, responsibility, humility, emotional control, the ability of the teachers to control emotions differently, some are good so that they think first before acting, polite, average the average teacher shows a polite attitude, both in speaking and behaving, exemplary by civilizing the S5, exemplary welcoming students in front of the gate, so that citizens of MAN 2 Kuningan can improve their religion (religious), change attitudes (akhlakul karimah), love to read and improve concern for the environment